A Trail of Trials. A 'Flemish' Merchant Community in Sixteenth-century Valladolid and Medina del Campo - Everaert, Janna (TSEG - The Low Countries Journal of Social and Economic History, 2017)
This article explores whether or not Flemish commercial networks reached the interior of the Iberian Peninsula and if so, how they functioned. By analysing the case of the Valladolid region through hitherto unexplored sources, this study shows that the economic opportunities offered by this region did not pass unnoticed by the Flemish merchants. While previous research focused on the conceptual dichotomy between ambulant and sedentary migration, this article shows that in practice, the Flemish merchant community in the Valladolid region covered the whole spectrum between these two positions. In fact, the hybrid nature of this Flemish merchant community seem to have been its strength as it connected different trade networks to each other and permitted the transfer of commercial expertise.